Intelectuais insurgentes no campo da formação de professores/as - Cardoso, Ivanilda Amado (2020)
In this research, I followed training paths based on the trajectory and production of black women and their inferences in educational spaces. The objective was to position insurgent intellectuals in the field of teacher education, representing the multiple voices of black teachers from the biography and bibliography of the Intellectual Insurgent Doctor Doctors Maria de Lourdes Siqueira, Ana Célia da Silva, Vanda Machado, Petronilha Beatriz Gonçalves and Silva and Joyce Elaine King. The field of teacher education is a space for the struggle for democracy and the realization of the anti-racist society project, so there is an emergency in the location of concepts and epistemologies that erase and question the pedagogical tendencies of Eurocentric bases. In this perspective, with input and methodological tool of the Escrevivência, intertwining and braiding memories and concepts, I present the dignified trajectory of life and interdisciplinary theoretical production available in books, articles, lectures and audiovisual material of the insurgent intellectuals as practical and theoretical potentials for the field of teacher training.